Perioperative aspiration events in children: A report from the Wake Up Safe Collaborative. Issue 6 (14th May 2020) - Pfaff, Kayla E.; Tumin, Dmitry; Miller, Rebecca; Beltran, Ralph J.; Tobias, Joseph D.; Uffman, Joshua C.
Abstract: Background: Perioperative aspiration, while rare, is a serious complication of anesthetic care. Consequences of aspiration may include physical obstruction, wheezing, and pneumonia, resulting in mild to severe hypoxemia and even death. Aim: We used a multi‐institutional registry of pediatric patients to identify factors that influence the rate and resulting harm of perioperative pulmonary aspiration. Methods: The Wake Up Safe registry was queried for all severe adverse events reported from 29 institutions from 2010 to 2017. Aspiration events were identified through the "respiratory adverse event" data entry form or through free text search. Multivariable regression was used to predict aspiration events, and contributory factors were identified by reviewing free text case comments. Results: Analysis included 2 440 810 anesthetics administered involving patients ≤18 years of age. There were 135 pulmonary aspiration events, for an incidence of 0.006%. Within these 135 cases, 110 cases (82%) resulted in escalation of care and 51 (38%) resulted in patient harm, including 2 deaths (1.5%). In multivariable analysis, patients undergoing emergency surgery (OR 2.0 [1.2‐3.5]) or with higher ASA status were more likely to experience aspiration (ASA 3 (OR 5.0 [2.6‐9.1]); ASA ≥ 4 (OR 5.5 [3.8‐16.8])). Noted causes of aspiration included gastrointestinal comorbid conditions (19%), postcoughing event or laryngospasm (14%), nil per os (NPO) violation (11%), blood or secretions in the airway following or during the procedure (6%), and oral premedication reaction (3%). Conclusion: Although infrequent, death was reported as a consequence of perioperative aspiration in two patients. The frequency with which NPO violations were identified as a potential cause of aspiration highlights the struggles institutions face with adherence to NPO regulations, as these cases may be preventable. Furthermore, preventive measures may be needed to address other common causes of aspiration, such as gastrointestinal comorbid conditions.